REKONSTRUKSI MANAJEMEN TALENTA ASN MENGGUNAKAN PENDEKATAN SOFT SYSTEM METHODOLOGY - Nurhakim Ramdani Fauzian (Institut Pemerintahan Dalam Negeri (IPDN), 2022)
The West Java Provincial Government has implemented talent management in their civil service management system, but still lack with the difficulty of finding suitable employees to be placed in top level manager. This study aims to reconstruct the management of the succession planning for senior civil service positions in the provincial government of West Java for the implementation of better talent management. The soft system methodology-based action research approach is used to find out the reality of the real problems in the management of succession planning for their senior civil service positions. Using SSM Based AR, the authors provide solutions in terms of a conceptual model framework for improving the civil service talent management in the West Java Provincial Government by defining and constructing Systematic Succession and Planning Management.